2023
DOI: 10.1088/1361-6560/acd29f
|View full text |Cite
|
Sign up to set email alerts
|

DMCT-Net: dual modules convolution transformer network for head and neck tumor segmentation in PET/CT

Abstract: Objective. Accurate segmentation of head and neck (H&N) tumors is critical in radiotherapy. However, the existing methods lack effective strategies to integrate local and global information, strong semantic information and context information, and spatial and channel features, which are effective clues to improve the accuracy of tumor segmentation. In this paper, we propose a novel method called dual modules convolution transformer network (DMCT-Net) for H&N tumor segmentation in the fluorodeoxyglucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additionally, oneFormer (Jain et al 2023) is a versatile segmentation model aiming to provide a new universal architecture for various types of image segmentation tasks. Moreover, in tumor segmentation (Wang et al 2023), cardiac segmentation (Lu et al 2023), polyp segmentation (Fu et al 2022), and other areas, deep learning has demonstrated significant potential. Image segmentation techniques can distinguish abnormal regions from normal ones in medical images, such as polyps.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, oneFormer (Jain et al 2023) is a versatile segmentation model aiming to provide a new universal architecture for various types of image segmentation tasks. Moreover, in tumor segmentation (Wang et al 2023), cardiac segmentation (Lu et al 2023), polyp segmentation (Fu et al 2022), and other areas, deep learning has demonstrated significant potential. Image segmentation techniques can distinguish abnormal regions from normal ones in medical images, such as polyps.…”
Section: Introductionmentioning
confidence: 99%